Keeping Calm and Carrying On: Relating Affect Spin and Pulse to Complex Skill Acquisition and Adaptive Performance - Richels, Kelsey A.; Day, Eric Anthony; Jorgensen, Ashley G.; Huck, Jonathan T. (Frontiers in Psychology, 2020)
The purpose of this laboratory study involving repeated measures of emotion as 214 undergraduates (58.4% male) learned a complex video game was to address the need for empirical research on dynamic personality constructs by examining how two aspects of affect variability—spin and pulse—explain variance in skill acquisition and adaptive performance. Spin refers to within-person fluctuations in affect pleasantness and activation potential. Pulse refers to within-person fluctuations in affect intensity. Despite research showing high affect variability reflects a personality profile of heighted reactivity to emotionally charged events and poor adjustment, little empirical research has examined their relationships with behavioral outcomes, much less aspects of skilled performance. Compared to traditional measures of personality, which yield weak effects for predicting acquisition and adaptive performance, measures of affect variability hold considerable promise because they, like performance, reflect dynamic within-person phenomena. Accordingly, the main question addressed by this study was whether spin and pulse incrementally explain acquisition and adaptive performance beyond Big Five measures of personality. In general, we expected harmful, incremental effects for both spin and pulse, and hypothesized two mechanisms for these harmful effects: (1) by undermining effort and (2) by undermining the effort-performance relationship. Using a task-change paradigm and discontinuous growth modeling that disentangled adaptation from acquisition, results showed that affect variability, independent of the Big Five, produced harmful effects via both hypothesized mechanisms. Participants higher in affect spin and pulse showed less sustained effort across performance sessions and exhibited lower performance. Furthermore, the harmful effects of spin and pulse were stronger in adaptation compared to acquisition, with pulse showing stronger direct effects on performance during adaptation and spin moderating the effort-performance relationship such that effort was only beneficial during adaptation for those lower in spin. In light of these results, one might question the common advice “keep calm and carry on,” which may not be viable for persons high in affect variability. Accordingly, results are discussed in terms of the need to better understand the specific mediating processes by which high affect variability undermines success across a variety of learning and performance contexts.